Legal Liability Peran Mucikari Terhadap Implementasi Undang-Undang TPPO di Makassar - Muhammad Yusuf Muhlis; Andi Mardaya; Elvi Susanti Syam; Afi Kamilia (Jurnal Litigasi Amsir, 2025)
This study aims to determine and analyze the implementation of legal provisions governing the responsibilities of pimps in eradicating the crime of human trafficking according to Law Number 21 of 2007 and what factors are obstacles in the investigation and inquiry process related to the role of pimps. This research uses a Normative Empirical research type with a Legislative Approach and a Social Approach. The data sources used are Primary Data and Secondary Data. Data analysis will be conducted using an observational-sensory and theoretical-rational approach using a reasoning model that first uses inductive logic and then continues with deductive logic. The implementation of legal provisions governing the responsibility of pimps in human trafficking crimes according to Law Number 21 of 2007 positions pimps as the main perpetrators, but in its application using Article 2 or 12 for pimps, it must be carried out with appropriate evidence in the practice of justice where law enforcers must prove the elements in the articles alleged to the pimp and supported by the attached evidence. In the implementation of criminal responsibility for pimps, the TPPO Law will provide an aggravating article for the crime if in his actions the pimp causes the victim to suffer mental and physical harm or even death. The implementation of criminal responsibility for pimps will be successful or fail depending on the law enforcement officers in the matter of evidence in the trial later and The implementation of legal provisions governing the responsibility of pimps in human trafficking crimes according to Law Number 21 of 2007 positions pimps as the main perpetrators, but in its application using Article 2 or 12 for pimps, it must be carried out with appropriate evidence in the practice of justice where law enforcers must prove the elements in the articles alleged to the pimp and supported by the attached evidence. In the implementation of criminal responsibility for pimps, the TPPO Law will provide an aggravating article for the crime if in his actions the pimp causes the victim to suffer mental and physical harm or even death.